2010
DOI: 10.21273/hortsci.45.4.566
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Rowcovers and Soil Amendments for Organic Cucumber Production: Implications on Crop Growth, Yield, and Microclimate

Abstract: The area of organic production has registered a steady increase over past recent years. Transitioning to organic production is not straightforward and often includes a steep learning curve. Organic growers have to develop strategies to best manage nutrients, pests, and crop growth and yield. Additionally, in regions with temperate climate like the Great Lakes region, weather (especially temperature and solar radiation) plays an important role in crop productivity. Growers routinely use compost for nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 29 publications
8
30
1
Order By: Relevance
“…The current results are similar to those reported by Nair and Ngouajio (2010) The increase in those parameters may have resulted from the increases in organic matter content in soil upon application of the organic amendments (Luan et al, 2019) and this would in turn, improve soil fertility (Dai et al, 2019;Mondal et al, 2019). The highest increases in curd height, diameter and fresh weight were recorded for plants amended with 14.4 m 3 ha -1 and irrigated with 85% of FI.…”
Section: Growth Parameters Of Cauliflower As Affected By Irrigation Asupporting
confidence: 89%
“…The current results are similar to those reported by Nair and Ngouajio (2010) The increase in those parameters may have resulted from the increases in organic matter content in soil upon application of the organic amendments (Luan et al, 2019) and this would in turn, improve soil fertility (Dai et al, 2019;Mondal et al, 2019). The highest increases in curd height, diameter and fresh weight were recorded for plants amended with 14.4 m 3 ha -1 and irrigated with 85% of FI.…”
Section: Growth Parameters Of Cauliflower As Affected By Irrigation Asupporting
confidence: 89%
“…Similar studies with muskmelon, tomato, and cucumber where sensors were 15 cm deep showed no differences in soil temperature between LT and open field (Tillman et al, 2015;Wolfe et al, 1989). By contrast, in studies that reported differences in soil temperatures, sensors were 5 cm deep (Arancibia and Motsenbocker, 2008;Nair and Ngouajio, 2010) and 10 cm deep (Ibarra et al, 2001;Ibarra-Jim enez et al, 2004;Soltani et al, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…They are semitransparent porous fabrics that allow airflow and ventilation, hence helping avoid condensation that may damage the foliage in contact with water (Arancibia, 2018). Low tunnels covered with spunbonded fabric increase vegetative growth and yield by increasing soil and air temperature (Arancibia, 2018;Arancibia and Motsenbocker, 2008;Gerber et al, 1988;Ibarra et al, 2001;Jolliffe and Gaye, 1995;Nair and Ngouajio, 2010). In addition, LTs are movable, allowing for crop rotation with cover crops in sustainable production systems.…”
mentioning
confidence: 99%
“…Gogo et al [23] also reported reduced pest attack, and higher yield and quality tomato from plants grown under net covers compared with open field. Similarly, Nair and Ngouajio (2010) [24] reported higher marketable yields of cucumber under nets compared with control.…”
Section: Effect On Yieldmentioning
confidence: 92%